REALIZING OF BREAST FEEDING IS NECESSARY OBJECTIVE OF A PEDIATRICIAN - I.A. Belyaeva ("Paediatrician" Publishers LLC, 2011)
The article analyzes several problems of breast feeding existing. The data on composition of breast milk in different groups of women, recommended terms of beginning and duration of breast feeding are presented. Authors discuss principles of effectiveness evaluation and advantages of prolonged breast feeding on the basis of comparative estimation of physical and psychical development and morbidity of children with different types of feeding. Methods of breast feeding optimization including modern electronic breast pump use are described.Key words: infants, breast feeding, breast pumps.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 86-91)